TaAMT2;3a, a wheat AMT2-type ammonium transporter, facilitates the infection of stripe rust fungus on wheat - Junpeng Jiang; Jing Zhao; Wanlu Duan; Song Tian; Xiaodong Wang; Hua Zhuang; Jing Fu; Zhensheng Kang (BMC Plant Biology, 2019)
Abstract Background Ammonium transporters (AMTs), a family of proteins transporting ammonium salt and its analogues, have been studied in many aspects. Although numerous studies have found that ammonium affects the interaction between plants and pathogens, the role of AMTs remains largely unknown, especially that of the AMT2-type AMTs. Results In the present study, we found that the concentration of ammonium in wheat leaves decreased after infection with Puccinia striiformis f. sp. tritici (Pst), the causal agent of stripe rust. Then, an AMT2-type ammonium transporter gene induced by Pst was identified and designated as TaAMT2;3a. Transient expression assays indicated that TaAMT2;3a was located to the cell and nuclear membranes. TaAMT2;3a successfully complemented the function of a yeast mutant defective in NH4 + transport, indicating its ammonium transport capacity. Function of TaAMT2;3a in wheat-Pst interaction was further analyzed by barley stripe mosaic virus (BSMV)-induced gene silencing. Pst growth was significantly retarded in TaAMT2;3a-knockdown plants, in which ammonium in leaves were shown to be induced at the early stage of infection. Histological observation showed that the hyphal length, the number of hyphal branches and haustorial mother cells decreased in the TaAMT2;3a knockdown plants, leading to the impeded growth of rust pathogens. Conclusions The results clearly indicate that the induction of AMT2-type ammonium transporter gene TaAMT2;3a may facilitates the nitrogen uptake from wheat leaves by Pst, thereby contribute to the infection of rust fungi.